Ekspresi AgNOR dan Ekspresi Ki-67 pada Grading Adenokarsinoma Prostat - Delyuzar; Roza Rita; Lidya Imelda Laksmi (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundProstate cancer is the second most common cancer and fifth most common cancer cause of death in males. Tissue biopsy is a goldstandard examination to diagnose prostate cancer. One of the hallmarks of cancer is increased activity of cell proliferation. Thisactivity can be detected with Ki-67 and AgNOR (Argyrophilic nucleolar organizing region). The aim of this study is to analyzedcorrelation between AgNOR and Ki-67 expression in grading of prostated adenocarcinoma.MethodsThis analytic cross-sectional study was held in Laboratory of Anatomical Pathology of Medical Faculty of USU/ RSUP H. AdamMalik Medan. Thirty paraffin blocks diagnosed with prostate adenocarcinoma were stained with H&E and p63 immunohistochemistrythen evaluated based on Gleason’s histopathological grading and stained with Agnor and Ki 67.ResultsAgNOR expression yang diperoleh pada grading adenokarsinoma prostat group 1, 2, 3, 4, dan 5 berturut-turut adalah 43; 32,40(±14,54); 64,29 (±28,2); 59,5 (±28,32); 69,22 (±29,26). Ekspresi Ki-67 pada setiap grading adenokarsinoma prostat group 1, 2, 3, 4,dan 5 secara berurutan adalah 43; 32,4 (±14,53); 64,29 (±28,2), 59,5 (±28,31); 69,22 (±29,26). Statistical analyses showed thatthere was no significantly correlation between grading of prostate adenocarcinoma and AgNOR expression (p=0.065), and Ki-67expression (p=0.18). Nevertheless, a significantly correlation between KI-67 expression and grading of prostate adenocarcinomawas found (p=0.34).ConclusionKi-67 could be used as prognostic indicator for prostate adenocarcinoma.